A preparation process of heptamethyltrisiloxane

By using a solid acid catalyst with active components such as γ-Fe2O3 and sulfonic acid groups, the problem of improper catalyst selection in the existing heptamethyl trisiloxane preparation process is solved, and a high-efficiency and stable catalytic effect and high-yield preparation process is achieved.

CN116462698BActive Publication Date: 2025-03-21YICHANG ZEMEI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310440345.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-03-21
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

In the existing preparation process of heptamethyltrisiloxane, improper catalyst selection leads to a wide distribution of product molecular weight, low product quality, and the catalyst is easily lost during the reaction, rapid reduction in activity, and inconvenient recovery.

Method used

A solid acid catalyst with porous carbon material supported active components is used, specifically including γ-Fe2O3 and sulfonic acid groups, with a molar ratio of 1:18-20. Combined with active ingredients such as WO3, ZnO, Al2O3, etc., a catalyst with magnetic properties and high stability is formed. It is suitable for the preparation of heptamethyltrisiloxane for polymerization of high hydrogen-containing silicone oil.

Benefits of technology

The catalytic efficiency and yield are improved, the reaction time is shortened, the product purification difficulty is reduced, the catalyst can be reused, the activity lasts for a long time, and the number of cycles is often repeated, and no particulate pore accumulation occurs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a preparation process of heptamethyltrisiloxane, wherein the catalyst used in the preparation process is formed by using a porous carbon material as a carrier to load an active component; the active component at least comprises γ-Fe2O3 and a sulfonic acid group, and the molar ratio of the two is 1:18-20. The preparation process of heptamethyltrisiloxane provided by the present invention is: using high hydrogen silicone oil as a raw material, under the action of a capping agent and the above-mentioned catalyst, a polyreaction is carried out at 40-95°C to obtain it. A new catalyst is used in the preparation process of heptamethyltrisiloxane of the present invention, and the catalyst has the advantages of high catalytic efficiency, low loss of active substances, and many reuse times. The heptamethyltrisiloxane obtained by the preparation process has high purity and is easy to separate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical industry, and in particular to a preparation process of heptamethyltrisiloxane. Background Art

[0002] 1,1,1,3,5,5,5-Heptamethyltrisiloxane (MD H M) is an important organosilicon intermediate. Because it contains active Si-H bonds, it is mainly used to synthesize Si-C type trisiloxane surfactants through hydrosilylation reaction with terminal allyl polyethers. Si-C type trisiloxane surfactants are the mainstream of current research and development due to their hydrolysis stability.

[0003] Currently, MD H The main methods for synthesizing M include halogenated silane co-hydrolysis, alkoxysilane condensation, ring-opening copolymerization, and high hydrogen silicone oil polymerization. Considering the reaction conditions and reaction process, the high hydrogen silicone oil polymerization has unique advantages. This method is to carry out polymerization reaction of high hydrogen silicone oil and hexamethyldisiloxane (MM) under acid-base catalysis. The process is relatively simple, the reaction conditions are mild, easy to control, the structure of the obtained product is closer to the designed structure, and the post-treatment is very simple, only filtering is required. For this reaction, the choice of catalyst is particularly important. The literature has reported that concentrated sulfuric acid or strong acid cation exchange resin was used as a catalyst, but the results were not ideal. When concentrated sulfuric acid is used as a catalyst, the product is not easy to separate, and neutralization and washing are required. The waste liquid pollutes the environment, and the catalytic effect is weak. The strong acid cation exchange resin itself has a high water content, resulting in a wide molecular weight distribution of the reaction product and low product quality.

[0004] In the study of acid-base catalysts, solid superacids, with their extraordinary acid strength, can enable many difficult chemical reactions to proceed under very mild conditions, becoming a hot topic in the field of catalysis. The solid surface acid strength of solid superacids is greater than 100% sulfuric acid, and it is a clean and pollution-free catalyst. Compared with liquid acid catalysts, solid superacids have better catalytic effects, less corrosive to equipment, less harmful to the environment, easy to separate from products, and can be reused.

[0005] The existing patent CN106317097B discloses a catalyst used for the preparation of low molecular weight siloxanes - a catalyst loaded with active substances Pt / SO4 2- / ZrO2 or Pt / WO3 / ZrO2 solid acid, the carrier is selected from alumina, silica gel, activated carbon, pumice, diatomaceous earth, etc. This solid acid is used for the preparation of low molecular weight siloxane by polymerization, and has the advantages of short reaction time, strong selectivity, narrow product molecular weight distribution, and high product yield. However, during the reaction of this catalyst, sulfate is easily lost, the activity will decrease rapidly, and ZrO2 has a small specific surface area, and a carbon layer is easily formed on the surface, which is coked and deactivated. When recovering the catalyst, there may be a problem of inconvenient recovery. Summary of the invention

[0006] The first object of the present invention is to provide a preparation process of heptamethyltrisiloxane, which has high catalytic efficiency, low difficulty in product purification and high yield.

[0007] The second object of the present invention is to provide a catalyst, which has high catalytic efficiency and strong reaction selectivity for preparing heptamethyltrisiloxane by polymerization; and the catalyst can be recycled by magnetic adsorption, has a long active duration, and can be recycled many times.

[0008] The third object of the present invention is to provide a method for preparing the above-mentioned catalyst, which has high production efficiency and high active component loading; the obtained catalyst has higher stability and orderliness and will not produce the phenomenon of particle accumulation pores.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0010] A method for preparing heptamethyltrisiloxane comprises the following steps: using high hydrogen silicone oil as a raw material, carrying out a telomerization reaction at 40-95° C. under the action of a capping agent and a catalyst, and after the reaction is completed, removing low boiling points in a vacuum and performing rectification to obtain the heptamethyltrisiloxane;

[0011] Among them, by weight, the amount of the high hydrogen silicone oil is 80-90 parts, the amount of the capping agent is 8-15 parts, and the amount of the catalyst is 2-5 parts; the catalyst is formed by a porous carbon material loaded with active components, and the active components contain at least γ-Fe2O3 and sulfonic acid groups, and the molar ratio of the two is 1:18~20.

[0012] γ-Fe2O3 is often used as a catalyst carrier due to its excellent redox ability. In the present invention, the inventors load it as an active ingredient together with sulfonic acid groups in a certain molar ratio. On the one hand, the combination of the two unexpectedly enhances the catalytic performance and stability of the solid acid, and on the other hand, it can give the catalyst magnetism and is easy to be recovered.

[0013] In some embodiments of the present invention, the carrier is selected from one or more of petroleum coke-based porous carbon, ordered mesoporous carbon and nanodiamond. Petroleum coke has a high carbon content and low volatile matter, and is a good raw material for preparing solid acid catalysts. Ordered mesoporous carbon has good hydrothermal stability and excellent mass transfer space due to its uniform pore structure. After activation, the surface of nanodiamond tends to form defect-rich graphene sheets, forming a "diamond-graphene" core-shell nanostructure, and the sp 3Hybridized carbon has good thermal conductivity, which can promote the heat transfer efficiency around the surface active sites and further promote the catalytic effect. These three have suitable shapes, sizes and mechanical strengths, and are more suitable for polymerization reactions when matched with active components. The inventors chemically activated the carrier to form a developed pore structure and a huge specific surface area inside it. The developed pore structure and huge specific surface area can provide good binding sites for the loaded active components, so that the obtained catalyst exhibits excellent catalytic performance in the reaction of participating in the preparation of heptamethyltrisiloxane, and the reaction yield can reach more than 50%.

[0014] In some embodiments of the present invention, the active component also introduces one of WO3, ZnO, and Al2O3, and the loading amount of the introduced WO3 and / or ZnO and / or Al2O3 is 0.5-1.5wt% of the total mass of the porous carbon material. After loading 0.5-1.5wt% of WO3 and / or ZnO and / or Al2O3 on the activated petroleum coke-based porous carbon, ordered mesoporous carbon or nanodiamond, the catalytic rate, component dispersibility and structural stability can be improved, which is specifically manifested in that after the catalyst completes the catalytic reaction, the acid density does not show a significant decrease, and the catalytic activity can still be maintained at a yield of more than 40% after multiple cycles. This is because under the action of the active component, there is no large-area carbon deposition on the surface of the solid acid catalyst, and the surface acid active sites can still maintain catalytic ability. Moreover, the inventors found during the experiment that if the active components such as WO3, ZnO, and Al2O3 are not added, the catalytic activity of the catalyst containing only γ-Fe2O3 and sulfonic acid active components decreases to a certain extent after multiple cycles.

[0015] In some embodiments of the present invention, the method for preparing the catalyst comprises the following steps:

[0016] S1: After the porous carbon material and potassium hydroxide are uniformly mixed, the temperature is raised to 350-450°C in a nitrogen flow, kept at this temperature for 1-2 hours, then raised to 700-800°C, kept at this temperature for 1-2 hours, and then cooled to room temperature;

[0017] S2: washing and drying the product obtained in step S1, mixing and grinding with concentrated sulfuric acid, and sulfonating under a nitrogen atmosphere at 150-200°C;

[0018] S3: Mix the sulfonated carrier in S2 with the mixed solution of ferrous chloride and ferric chloride, add sodium tungstate or zinc acetate or aluminum nitrate solution, add alkali solution to adjust the pH to 9-10, transfer to the reactor, heat to 120-150°C and keep for 2-3h;

[0019] S4: The product obtained in S2 is cooled, centrifuged, washed, dried, and calcined at 300-400° C. for 3-5 hours to obtain the catalyst.

[0020] In some embodiments of the present invention, the mixing mass ratio of the porous carbon material to potassium hydroxide in step S1 is 1:2.5-3; the solid-liquid mixing ratio of the activated porous carbon material to concentrated sulfuric acid in step S2 is 1g:100-120ml, and the sulfonation time is 9-10h; the mixed molar concentration of ferrous ions and ferric ions in the mixed solution of ferrous chloride and ferric chloride in step S3 is 0.1-0.5mol / L, and the volume ratio of the mixed solution of ferrous chloride and ferric chloride to the concentrated sulfuric acid used is 1:5-10.

[0021] The inventors found that in step S2, if the concentrated sulfuric acid is used in excess, the activated porous carbon material will be over-carbonized, the formed pore structure will be destroyed, and the subsequent active component loading cannot be achieved. In addition, the dehydration condensation of hydroxyl and carboxyl groups on the carrier may be catalyzed, affecting the performance of the catalyst. Therefore, the concentrated sulfuric acid used for sulfonation should be appropriate.

[0022] In some embodiments of the present invention, the end-capping agent in the preparation process of heptamethyltrisiloxane can be any suitable siloxane end-capping agent, preferably one or more combinations of hexamethyldisiloxane, trimethylmethoxysilane, and trimethylsilanol.

[0023] Beneficial effects: Compared with the prior art, the present invention has achieved the following technical effects: the preparation process provided by the present invention has a short reaction cycle, the time used is no more than 7 hours, and the homemade catalyst used has high catalytic efficiency, convenient recovery, and can be repeated many times, which are specifically manifested in: shortened reaction time, improved yield, and product yield of more than 50%; because of the magnetism of γ-Fe2O3, it is also easy to operate when recovering the catalyst. In addition, the presence of the three active ingredients WO3, ZnO and Al2O3 can make the acid active sites of the catalyst more stable, inhibit the carbonization of the catalyst surface, and still have good catalytic efficiency after multiple cycles. The preparation process of the present invention does not require neutralization and washing after the reaction is completed, and only fractionation is required to obtain high-purity heptamethyltrisiloxane. DETAILED DESCRIPTION

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0025] The preparation of the catalyst used in the examples and comparative examples is exemplarily described below:

[0026] Catalyst-1

[0027] S1: After the petroleum coke-based porous carbon and potassium hydroxide are uniformly mixed in a mass ratio of 1:2.5, the temperature is raised to 350°C in a nitrogen flow, kept at this temperature for 1 hour, then raised to 700°C, kept at this temperature for 1 hour, and then cooled to room temperature;

[0028] S2: After washing and drying the product obtained in step S1, the product was mixed and ground with concentrated sulfuric acid at a solid-liquid ratio of 1 g:100 ml, and sulfonated at 150° C. in a nitrogen atmosphere for 9 hours;

[0029] S3: The sulfonated petroleum coke-based porous carbon in S2 is mixed with a mixed solution containing 0.002 mol of ferrous chloride and 0.008 mol of ferric chloride, and the volume ratio of the mixed solution to the concentrated sulfuric acid is 1:5. Then 0.005 mol of sodium tungstate is added, the pH is adjusted to 9-10, and the mixture is transferred to a reactor, heated to 120°C and maintained for 2 hours;

[0030] S4: The product obtained in S2 is cooled, centrifuged, washed, dried, and calcined at 300° C. for 3 h to obtain the catalyst-1.

[0031] Catalyst-2

[0032] S1: After the ordered mesoporous carbon and potassium hydroxide are uniformly mixed in a mass ratio of 1:2.8, the temperature is raised to 400°C in a nitrogen flow, kept at this temperature for 2 hours, then raised to 700°C, kept at this temperature for 1 hour, and then cooled to room temperature;

[0033] S2: After washing and drying the product obtained in step S1, the product was mixed and ground with concentrated sulfuric acid at a solid-liquid ratio of 1 g:110 ml, and sulfonated at 180°C in a nitrogen atmosphere for 9 hours;

[0034] S3: The sulfonated ordered mesoporous carbon in S2 is mixed with a mixed solution containing 0.003 mol ferrous chloride and 0.007 mol ferric chloride, and the volume ratio of the mixed solution to the concentrated sulfuric acid is 1:10. Then 0.02 mol zinc acetate is added, the pH is adjusted to 9-10, and the mixture is transferred to a reactor, heated to 130°C and maintained for 2 hours;

[0035] S4: The product obtained in S2 is cooled, centrifuged, washed, dried, and calcined at 350° C. for 4 h to obtain the catalyst-2.

[0036] Catalyst-3

[0037] S1: After mixing nanodiamond and potassium hydroxide in a mass ratio of 1:3, the mixture was heated to 450°C in a nitrogen flow, kept at this temperature for 2 hours, then heated to 800°C, kept at this temperature for 2 hours, and then cooled to room temperature;

[0038] S2: After washing and drying the product obtained in step S1, the product was mixed and ground with concentrated sulfuric acid at a solid-liquid ratio of 1 g:120 ml, and sulfonated at 200° C. for 10 h in a nitrogen atmosphere;

[0039] S3: Mix the sulfonated nanodiamond in S2 with a mixed solution containing 0.005 mol ferrous chloride and 0.005 mol ferric chloride, with the volume ratio of the mixed solution to the concentrated sulfuric acid being 1:6. Add 0.04 mol aluminum nitrate, adjust the pH to 9-10, transfer to a reactor, heat to 150°C and keep for 3 hours;

[0040] S4: The product obtained in S2 is cooled, centrifuged, washed, dried, and calcined at 400° C. for 5 h to obtain the catalyst-3.

[0041] Catalyst-4

[0042] The difference from Catalyst-1 is that the solid-liquid ratio of the carrier to concentrated sulfuric acid is 1g:150mL.

[0043] Catalyst-5

[0044] The difference from Catalyst-1 is that no sodium tungstate is added.

[0045] The qualitative and quantitative analysis of the components of Catalyst-1 to Catalyst-5 is shown in Table 1 below:

[0046]

[0047] Example 1

[0048] In a 500mL three-necked flask equipped with a mechanical stirrer, a thermometer and a reflux condenser, 80 parts of high hydrogen silicone oil (the hydrogen content of the high hydrogen silicone oil is 1.60%), 8 parts of hexamethyldisiloxane as a capping agent and 2 parts of catalyst-1 were added, the temperature was raised to 40°C for polymerization for 4 hours under stirring, the catalyst-1 was filtered out, the temperature was gradually raised to 90°C at 5 mmHg to remove low boiling points, and the temperature was raised to 145°C for distillation to obtain a colorless transparent oil with a yield of 55.11%.

[0049] Example 2

[0050] The operation was the same as in Example 1. The raw materials and operating conditions were: 85 parts of high hydrogen silicone oil (the hydrogen content of the high hydrogen silicone oil was 1.60%), 10 parts of trimethylmethoxysilane, and 4 parts of -catalyst-2; polymerization was carried out at 65°C for 5 hours, and the yield was 56.26%.

[0051] Example 3

[0052] The operation was the same as in Example 4. The raw materials and operating conditions were: 90 parts of high hydrogen silicone oil (the hydrogen content of the high hydrogen silicone oil was 1.60%), 15 parts of trimethylmethoxysilane, and 5 parts of -catalyst-3; polymerization was carried out at 95°C for 5 hours, and the yield was 53.03%.

[0053] Example 4

[0054] The operation was the same as in Example 1, except that the catalyst used was Catalyst-4, and the yield was 51.81%.

[0055] Example 5

[0056] The operation was the same as in Example 1, except that the catalyst used was Catalyst-5, and the yield was 50.55%.

[0057] Comparative Example 1

[0058] The operation was the same as in Example 1, except that the catalyst used was concentrated sulfuric acid, and the yield was 30.32%.

[0059] Comparative Example 2

[0060] The operation was the same as in Example 1, except that the catalyst used was a solid acid catalyst HND-31 purchased from Angxing New Carbon Materials Changzhou Co., Ltd. At the end of the reaction, the catalyst had broken, the reaction system was yellow-brown, and the yield was 34.41%.

[0061] The reaction results of Examples 1-5 and Comparative Examples 1-2 are detailed in Table 2 below:

[0062]

[0063] As can be seen from Table 1 and Table 2, the yield of heptamethyltrisiloxane prepared by the preparation process provided by the present invention is above 50%, and the homemade catalyst used has a higher active specific surface area, has a higher catalytic efficiency than the conventional catalyst concentrated sulfuric acid and the solid acid catalyst HND-31, and is easy to recycle; after multiple cycles, a higher active specific surface area is still maintained. Using the homemade catalyst of the present invention, high hydrogen silicone oil is used as a raw material, and heptamethyltrisiloxane is prepared by the improved telomerization method, which is simple to operate, has a short reaction cycle, and the product is easy to extract and has high purity.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for preparing heptamethyltrisiloxane, characterized in that: include: The high hydrogen silicone oil, the end-capping agent and the catalyst are mixed, and a telomerization reaction is carried out at 40-95° C. After the reaction is completed, the low-boiling substances are removed by vacuum and distillation to obtain the heptamethyltrisiloxane; wherein the catalyst is formed by a porous carbon material loaded with active components, and the active components at least contain γ-Fe2O3 and sulfonic acid groups, and the molar ratio of the two is 1:18-20; The active component further comprises one of WO3, ZnO, and Al2O3; The loading amount of WO3 and / or ZnO and / or Al2O3 is 0.5-1.5wt% of the total mass of the porous carbon material.

2. The process for preparing heptamethyltrisiloxane according to claim 1, characterized in that: The porous carbon material is selected from one or more of petroleum coke-based porous carbon, ordered mesoporous carbon and nanodiamond.

3. The process for preparing heptamethyltrisiloxane according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: S1: After the porous carbon material and potassium hydroxide are uniformly mixed, the temperature is raised to 350-450°C in a nitrogen flow, kept at this temperature for 1-2 hours, then raised to 700-800°C, kept at this temperature for 1-2 hours, and then cooled to room temperature; S2: washing and drying the product obtained in step S1, mixing and grinding with concentrated sulfuric acid, and sulfonating under a nitrogen atmosphere at 150-200°C; S3: Mix the sulfonated carrier in S2 with the mixed solution of ferrous chloride and ferric chloride, add sodium tungstate or zinc acetate or aluminum nitrate, add alkali solution to adjust the pH to 9-10, transfer to the reactor, heat to 120-150°C and keep for 2-3h; S4: The product obtained in S3 is cooled, centrifuged, washed, dried, and calcined at 300-400° C. for 3-5 hours to obtain the catalyst.

4. The process for preparing heptamethyltrisiloxane according to claim 3, characterized in that: In the step S1, the mixing mass ratio of the porous carbon material to potassium hydroxide is 1:2.5-3.

5. The process for preparing heptamethyltrisiloxane according to claim 3, characterized in that: In the step S2, the solid-liquid mixing ratio of the activated porous carbon material and concentrated sulfuric acid is 1 g:100-120 ml, and the sulfonation time is 9-10 h.

6. The process for preparing heptamethyltrisiloxane according to claim 3, characterized in that: The mixed molar concentration of ferrous ions and ferric ions in the mixed solution of ferrous chloride and ferric chloride is 0.1-0.5 mol / L.

7. The process for preparing heptamethyltrisiloxane according to claim 3, characterized in that: In step S3, the volume ratio of the mixed solution of ferrous chloride and ferric chloride to concentrated sulfuric acid is 1:5-10.

8. The process for preparing heptamethyltrisiloxane according to claim 1, characterized in that: The end-capping agent is one or more combinations of hexamethyldisiloxane, trimethylmethoxysilane and trimethylsilanol.

Citation Information

Patent Citations

  • Low molecular weight siloxanes and their preparation methods, catalysts used and their preparation methods

    CN106317097B

  • Novel method for preparing 1,1,1,3,5,5,5-heptamethyltrisiloxane by adopting solid superacid

    CN104004010A